Supplementary role of left ventricular global longitudinal strain for predicting sudden cardiac death in hypertrophic cardiomyopathy. (20th September 2021) - Lee, Hyun Jung; Kim, Hyung Kwan; Lee, Sang Chol; Kim, Jihoon; Park, Jun Bean; Hwang, In Chang; Choi, You Jung; Lee, Seung Pyo; Chang, Sung A; Lee, Whal; Park, Eun Ah; Cho, Goo Yeong; et al.
Abstract: Aims: We investigated the prognostic role of left ventricular global longitudinal strain (LV-GLS) and its incremental value to established risk models for predicting sudden cardiac death (SCD) in patients with hypertrophic cardiomyopathy (HCM). Methods and results: LV-GLS was measured with vendor-independent software at a core laboratory in a cohort of 835 patients with HCM (aged 56.3 ± 12.2 years) followed-up for a median of 6.4 years. The primary endpoint was SCD events, including appropriate defibrillator therapy, within 5 years after the initial evaluation. The secondary endpoint was a composite of SCD events, heart failure admission, heart transplantation, and all-cause mortality. Twenty (2.4%) and 85 (10.2%) patients experienced the primary and secondary endpoints, respectively. Lower absolute LV-GLS quartiles, especially those worse than the median (−15.0%), were associated with progressively higher SCD event rates ( P = 0.004). LV-GLS was associated with an increased risk for the primary endpoint, independent of the LV ejection fraction, apical aneurysm, and 2014 European Society of Cardiology (ESC) risk score [adjusted hazard ratio (aHR) 1.14, 95% confidence interval (CI) 1.02–1.28] or 2011 American College of Cardiology/American Heart Association (ACC/AHA) risk factors (aHR 1.18, 95% CI 1.05–1.32). LV-GLS was also associated with a higher risk for the composite secondary endpoint (aHR 1.06, 95% CI 1.01–1.12). The addition of LV-GLS enhanced the performance of the ESC risk score ( C -statistic 0.756 vs. 0.842, P = 0.007) and the 2011 ACC/AHA risk factor strategy ( C -statistic 0.743 vs. 0.814, P = 0.007) for predicting SCD. Conclusion: LV-GLS is an important prognosticator in patients with HCM and provides additional information to established risk stratification strategies for predicting SCD. Graphical Abstract: